All Inclusive - Hecher, Beate; Keim, Markus (Austria, 2012)
An apocalyptic colonial composition that focuses on a panoramic view of a hotel ruin in the Eygptian desert, a depraved despot in snorkeling gear, protests, the report of a hotel manager about the supply situation in of WWI in Egypt, sounds of shots and screams, and an interrupted telephone connection. Attempts to demonstrate the lost past.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films